IMPORTANCE OF ORGANIC PETROLOGY TO TYPE AND RANK OF MIOCENE ASEM-ASEM COAL-SOUTH KALIMANTAN - BINARKO SANTOSO; BUKIN DAULAY (Indonesian Mining Journal, 2008)
The Asem-Asem Basin has cratonic and back-arc settings containing coal deposits that were formed in Tertiary sequences. The coals were deposited in fluvial to deltaic environments. Megascopically, the coals are dominated by bright-banded and banded lithotypes. Microscopically, vitrinite and liptinite are the dominant macerals in the Miocene coals. Inertinite is a minor component and mineral content is also low in most of the coals. There is significant relationship between megas- copic and microscopic observations; the brighter coal is in association with the vitrinite-rich coal, otherwise, the duller coal is in association with the inertinite-rich coal with relatively high mineral content. The differences in the coal type are due to the interaction of tectonic, geologic, palaeoclimate and plant evolutionary factors. The ranks of the Miocene coals ranging from brown coal to high volatile bituminous indicate a normal regional coalification. Most of the coals are suitable for feedstocks in combustion that is the most important present day use for coals.